(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تعد الدوامة البحرية المسماة بيلوبسPelops دوامة أنتيسكلونية متشكلة بفعل رياح الإتزيان (Etesian) في جنوب أو جنوب-غرب الجزر اليونانية Peloponese . لدراسة سلوك هذه الدوامة وخصائصها، تمت معالجة بعض القياسات الحقلية البحرية (XBT : eXpendable Bathy-Thermograph) وتحليلها في المنطقة المذكورة ومن ثم مقارنتها بنتائج تحليل صور الأقمار الصناعية SST (Sea Surface Temperature ، صور تعتمد الأشعة تحت الحمراء حيث تعطي درجات الحرارة لسطح البحر). كشفت هذه المقارنة عن وجود تطابق ملحوظ بين نتائج تحليل كل المعطيات السابقة. تجاوز قطر الدوامة 230 km أما امتدادها في الأعماق، كما بينت نتائج تحليل القياسات الحقلية، فهو على الأقل .760 m Pelops is a mesoscale anticyclonic eddy generated by the Etesian in the south or south-west of the Peloponese Island. Some in situ data (XBT: eXpendable Bathy-Thermograph), have been treated and analyzed to study Pelops and this data results analysis have been confronted with those of the infrared satellite images (SST: Sea Surface Temperature). There are good agreements between both data. Eddy’s diameter passed 230 km and its extension at depth, as the in situ data inferred, is at least 760m.